Microtubule depolymerization promotes particle and chromosome movement in vitro (The Rockefeller University Press, 1991)
We have developed a system for studying the motions of cellular objects attached to depolymerizing microtubules in vitro. Radial arrays of microtubules were grown from lysed and extracted Tetrahymena cells attached to a glass coverslip that formed the top of a light microscope perfusion chamber. A preparation of chromosomes, which also contained vesicles, was then perfused into the chamber and allowed to bind to the microtubule array. The concentration of tubulin was then reduced by perfusing buffer that lacked both tubulin and nucleotide triphosphates, and the resulting microtubule depolymerization was observed by light microscopy. A fraction of the bound objects detached in the flow and washed away, while others stabilized the microtubules to which they were bound. Some of the particles and chromosomes, however, moved in toward the Tetrahymena ghost as their associated microtubules shortened. The mean speeds for particles and chromosomes were 26 +/- 20 and 15 +/- 12 microns/min, respectively. These motions occurred when nucleotide triphosphate levels were very low, as a result of either dilution or by the action of apyrase. Furthermore, the motions were unaffected by 100 microM sodium orthovanadate, suggesting that these forces are not the result of ATP hydrolysis by a minus end-directed mechanoenzyme. We conclude that microtubule depolymerization provided the free energy for the motions observed. All the objects that we studied in detail moved against a stream of buffer flowing at approximately 100 microns/s, so that the force being developed was at least 10(-7) dynes. This force is large enough to contribute to some forms of motility in living cells.